2010
DOI: 10.1021/ma101465z
|View full text |Cite
|
Sign up to set email alerts
|

Bond−Vector Correlation Functions in Dense Polymer Systems

Abstract: It is well-known that homopolymer chains do not exactly follow the Gaussian statistics even in the melt state. In particular, orientations of two bonds l 1 and l 2 of the same chain in a concentrated polymer system are always correlated even when they are separated by a long segment of s . 1 units: AEl 1 3 l 2 ae s = C(s) ∼ 1/s 3/2 . It is important to know how these orientational correlations are distributed in space, i.e. how AEl 1 3 l 2 ae depends on the distance r between the bonds. 1 An unexpected feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 15 publications
0
22
1
Order By: Relevance
“…For small p/N (large N/p), one should expect that 4 sin 2 (pπ/(2N )) X 2 p reaches a plateau value b 2 . However, since at short length scale the local intramolecular correlations in the chains (the correlation hole effect) are important, a correction term [8,9,16] O((N/p) −1/2 ) is needed to be considered as follows,…”
Section: Rouse Mode Analysismentioning
confidence: 99%
“…For small p/N (large N/p), one should expect that 4 sin 2 (pπ/(2N )) X 2 p reaches a plateau value b 2 . However, since at short length scale the local intramolecular correlations in the chains (the correlation hole effect) are important, a correction term [8,9,16] O((N/p) −1/2 ) is needed to be considered as follows,…”
Section: Rouse Mode Analysismentioning
confidence: 99%
“…Recently, it was emphasized 12 , 13 that the intramolecular bond correlation function in dense melts decays as a power law in contrast to an exponential decay for chains without long-range correlations. This leads to a partial swelling of polymer chains even in monodisperse melts with the mean square radius of gyration of a chain with n monomers approximated 12 by with characteristic ratio The coefficient c = 0.656, root-mean-square bond length l = 2.636, and C ∞ = 1.52 were determined in ref ( 12 ) at simulation conditions identical to the present study.…”
mentioning
confidence: 99%
“…The traditional one is defined through the exponential decay of the orientational correlation function 〈cos θ( s )〉 (Equation ). Although for both random walk and self‐avoiding walk the orientational correlation function shows a power law decay behavior at a large length scale s > s *, this stays a good estimator considering that it can recover the stiffness parameter κ (Figure ) and that l p should not depend on the polymer length ( Figure blue solid line). Another way is to calculate l p from Equation or simply Re2/ 2Nblb when L is large enough.…”
Section: Resultsmentioning
confidence: 77%
“…The continuous version of the Kratky‐Porod model is the worm‐like chain model, where the persistence length l p is defined through the exponential decay of the orientational correlation function: u(s1+s)u(s1)=cosθ(s)=es/lpHere u(s)=r(s)s is the unit tangent vector to the chain at contour distance s , and r(s) is the position vector along the chain. Although chains in a dense melt or at the Θ‐point in solution behave like ideal chains without excluded volume effect, as the worm‐like chain does, recently it was shown that the orientational correlation function for chains in these conditions shows a power law decay s −3/2 instead of the above exponential decay for certain range of contour length 1 ≪ s ≪ N . For real chains Hsu et al .…”
Section: The Modelmentioning
confidence: 99%